2020
DOI: 10.1080/15384101.2020.1744976
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of microRNA-584 promotes dental pulp stem cells proliferation by targeting TAZ

Abstract: Proliferation of dental pulp stem cells (DPSCs) is crucial in tooth development and damage repairing, also includes its therapy application for tissue engineering. MicroRNAs (miRNAs) are key players in biological processes of DPSCs, and transcriptional co-activator with PDZ-binding motif (TAZ) also plays important roles in cell proliferation and differentiation, however, the roles of miR-584 and TAZ in DPSCs are not known. We found up-regulated miR-584 expression and downregulated TAZ expression levels in agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…For YAP, the only upstream regulatory transcription factor reported so far is cyclic adenosine monophosphate response element-binding protein (CREB) [46]. In cancer, both YAP and TAZ RNA are frequently increased, but the mechanisms behind this upregulation remain largely elusive and may involve both transcriptional and post-transcriptional mechanisms through suppression of the YAP/TAZ regulatory microRNAs, including miR-15a, miR-141-3p, mir-194, miR-195, miR-375, miR-381, miR-584, miR-125, miR-185, miR-9-3p and miR-129-5p, to name a few [47][48][49][50][51][52][53][54][55][56][57].…”
Section: Transcriptional and Post-transcriptional Regulators Of Yap Amentioning
confidence: 99%
“…For YAP, the only upstream regulatory transcription factor reported so far is cyclic adenosine monophosphate response element-binding protein (CREB) [46]. In cancer, both YAP and TAZ RNA are frequently increased, but the mechanisms behind this upregulation remain largely elusive and may involve both transcriptional and post-transcriptional mechanisms through suppression of the YAP/TAZ regulatory microRNAs, including miR-15a, miR-141-3p, mir-194, miR-195, miR-375, miR-381, miR-584, miR-125, miR-185, miR-9-3p and miR-129-5p, to name a few [47][48][49][50][51][52][53][54][55][56][57].…”
Section: Transcriptional and Post-transcriptional Regulators Of Yap Amentioning
confidence: 99%
“…The transcriptional coactivator with PDZ-binding motif (TAZ) is reported to be essential for the proliferation of DPSCs. TAZ can be silenced by miR-584, which binds directly to TAZ mRNA and in turn suppresses the proliferation [ 146 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…ALPL is a very important osteogenic regulatory gene. Tian et al (2020) found that inhibiting miR-584-5p in dental pulp stem cells can promote cell proliferation. Therefore, we chose miR-584-5p for follow-up experiments.…”
Section: Resultsmentioning
confidence: 99%